Comparison of multilevel PWM versus interleaved based sinewave shaping for two-stage current source inverters used in PV applications - Papadopoulos, Savvas; Klumpner, Christian (2013)
This paper investigates the advantages of using interleaved based direct sinusoidal current shaping techniques as alternative to 5-level Pulse Width Modulation (PWM) when used in conjunction to a two stage Current Source Inverter (CSI) in PV applications. By using simulation based modelling it is proven that; in combination with switching harmonic cancellation techniques; for a given output power, direct shaping allows for better utilization of devices and subsequently the minimization of losses without sacrificing power quality.